Selective vs. Collective Outcomes of Collaborative Governance: The Impacts of Federal Stimulus Programs on Local and Regional Governance Outcomes - Chang-Gyu Kwak (MDPI AG, 2021)
A number of studies have demonstrated that local government’s self-governing mechanisms can bring about positive collective outcomes for an entire region. However, less attention has been paid to different levels of collective outcomes (e.g., individual local governments vs. entire regions). Comparing such selective and collective outcomes in interlocal collaborations, this study attempts to explore which specific collaborative self-governing mechanisms can better work for which respective outcomes. Applying network approaches with time-series cross-sectional data, this study investigates how each local government’s network position and the network structure as a whole influence the impact of Energy Efficiency and Conservation Block Grants on job creation in terms of the regional green economy. Empirical results demonstrate the need for separating selective and collective outcomes in developing theories of regional governance. Additionally, the results provide practitioners with advice on how to manage interlocal relationships in order to maximize collective outcomes at different levels